EU Migration Law Shaping International Migration Law in the Field of Expulsion of Aliens: The Empire Strikes Back? - Molnár, Tamás (Pécs journal of international and European law, 2017)
Since the Treaty of Maastricht, EU law has become more open to international law and engaged with it in different forms of interactions. Influence of EU law on universal law-making finds its way through different legal channels and techniques. The article thoroughly scrutinizes the impact of EU return acquis on the development of the international law governing the ‘expulsion of aliens’, which can be best analysed through the work of the UN International Law Commission on the expulsion of aliens (2004-2014). For the ILC’s approach, it has come a long way from the mere ignorance of EU law and the EU’s submissions by the special rapporteur in the early stages of the codification work until gradually taking into account major EU migration law concepts in ILC reports and in the draft articles. The 2014 ILC draft articles on the expulsion of aliens have finally been in many aspects inspired and influenced by EU law, especially the Return Directive (2008/115/EC). This short piece meticulously explores the inroads EU return law made in relation to the ILC work on the expulsion of aliens, by identifying and critically evaluating the tangible impact of EU law on the UN codification project.